A REVIEW ON RELIABILITY ASSESSMENT FOR PROTECTION SYSTEMS OF HIGH VOLTAGE TRANSMISSION SYSTEM - Gencaydin, Ender; Tanrioven, Mugdesem (YILDIZ TECHNICAL UNIV, 2013)
Protection engineering is the branch of electrical power engineering concerned with the design and operation of protection systems. The purpose of protection system is to minimize the effects of faults on electrical power systems. In this study, reliability evaluation of protection systems which play vital role in maintaining power systems is done. General information about protection systems and the equipment that been consisted of protection systems are given; general definition of reliability is done; general reliability model of a protection relay, space state model of a protection relay and reliability indices of a protection relay is given; the studies which are related to reliability of protection systems that has been done in literature lately are presented; influence of current transformers on protection relay reliability and a numerical application which explains selection criteria of current transformers is investigated, influence of non-sinusoidal condition on protection relay reliability for electromechanical, static and numeric protection relays are looked into.
Keywords: Reliability; protection systems; protection relay; current transformer; harmonics; Engineering